The economic costs of war by other means - Sonali Chowdhry; Gabriel Felbermayr; Julian Hinz; Katrin Kamin; Anna-Katharina Jacobs; Hendrik Mahlkow (Kiel Institute for the World Economy (IfW), 2020)
Military interventions and economic sanctions are increasingly seen as strategic substitutes for achieving national and global security objectives, both impose economic costs. We quantify the lower bound of the costs of sanctions using a gravity model of international trade and a general equilibrium simulation model. We find that sanctions amount to a loss in GDP of about 34 billion USD in 2019/2020 for the sanctioning NATO countries collectively, but the costs of sanctions are very unevenly distributed. No other country contributes as much as Germany (8.1 billion USD), while the costs for the US amount to 2.6 billion USD. Accounting for sanctions, countries' contributions to global security as a share of GDP are closer to the 2% NATO target than a narrow focus on military expenditure alone would suggest. Hence, there is less free-riding than some observers suspect. – – Militärische Interventionen werden zunehmend durch Sanktionen ersetzt, um außenpolitische Ziele der globalen Sicherheit zu verfolgen. Beide Mittel verursachen ökonomische Kosten. Anhand des Gravitationsmodells des internationalen Handels und eines allgemeinen Gleichgewichtsmodells quantifizieren wir die Untergrenze von Sanktionskosten. Die Sanktionen implizieren für die sanktionierenden NATO-Staaten im Jahr 2019/2020 einen BIP-Verlust von rund 34 Mrd. USD. Diese Sanktionskosten sind jedoch sehr ungleich verteilt. Kein anderes Land trägt so viel zu den Sanktionskosten bei wie Deutschland (8,1 Milliarden USD), während die Kosten für die USA weniger als 2,6 Milliarden USD betragen. Bezieht man die Sanktionskosten mit ein, liegen die Beiträge der Länder zur globalen Sicherheit als Anteil am BIP näher am NATO-Ziel von 2%, als ein enger Fokus auf die Militärausgaben allein vermuten lässt. In Bezug auf Beiträge zur globalen Sicherheit gibt es daher weniger Trittbrettfahren als manche Beobachter vermuten.
Keywords: 330; sanctions; NATO; trade policy; global security; Sanktionen; NATO; Handelspolitik; globale Sicherheit